Threshold in North Atlantic-Arctic Ocean circulation controlled by the subsidence of the Greenland-Scotland Ridge - Michael Stärz (Nature Portfolio, 2017)
During the Cenozoic the Arctic Ocean change from a restricted freshwater regime towards more saline modern ocean conditions is supposedly driven by the subsidence of the Greenland-Scotland Ridge. Here, the authors derive a threshold for this shift, constrained by the characteristic depth of wind mixing.